Chemical Optimization for Simultaneous Voltammetric Detection of Molybdenum and Silver Nanoparticles in Aqueous Buffer Solutions. Issue 12 (22nd September 2014) - Goda, Tatsuro; Oohashi, Mikiya; Matsumoto, Akira; Hoshi, Toru; Sawaguchi, Takashi; Pumera, Martin; Miyahara, Yuji
Abstract Simultaneous acquisition of redox signals from different types of metal nanoparticles (NPs) in a multiplexing system requires a good separation in redox potential from each component for successful identification. The appearance of a single distinct peak for each NP type is also preferred. Here, we report variations in the electrochemical nature of molybdenum (Mo) and silver (Ag) NPs cast on a glassy carbon electrode that are sensitive to various conditions of the measurement solution, such as buffering capacity and electrolyte concentration. A series of experiments allowed us to find optimal conditions, where Mo NPs showed a single oxidation peak with good separation of the redox potential from that of Ag NPs (ΔE≈0.25 V), by using differential‐pulse voltammetry (DPV). In the simultaneous monitoring of Mo and Ag NPs under the optimal conditions, the peak currents in DPV were quantitative for the amount of Mo/Ag NPs ranging from 7.8/20 to 500/20 ng ng−1 and from 500/20 to 500/0.31 ng ng−1.